Annual reproductive cycle of males of the great fruit-eating bat, Artibeus lituratus: Testicular variations, abiotic regulation and sperm analysis - Andrade, Cleber S. (2023)
Artibeus lituratus is one of the most well-known bat species in the Neotropics, probably due to its high abundance and the ability to inhabit urban areas. It plays an important ecological role in the ecosystem due to its ability to disperse seeds, which contributes to the regeneration of degraded areas. Actually, the species has been used as an important experimental model for ecotoxicological studies of the impact of pesticides on male reproduction. Despite that, the reproductive pattern of A. lituratus is still controversial due to inconsistent descriptions of the reproductive cycle. Thus, the aim of the present work was to evaluate the annual variations of the testicular parameters and sperm quality of A. lituratus and analyze their responses to annual variations in abiotic factors in the Cerrado area in Brazil. Testes of five specimens were collected each month for one year (12 sample groups) and submitted to histological, morphometric, and immunohistochemical analyses. Analyses of the sperm quality were also performed. Results demonstrate that A. lituratus presents a continuously active process of spermatogenesis throughout the year, with two significant peaks in spermatogenic production (September-October and March), which indicates a bimodal polyestric pattern of reproduction. These reproductive peaks seem to be related to an increase in proliferation and, consequently, in the number of spermatogonia. Conversely, seasonal variations in testicular parameters are correlated with annual fluctuations in rainfall and photoperiod but not with temperature. In general, the species presents smaller spermatogenic indexes with a similar sperm quantity and quality to other bat species.